Influence of Physically Active or Sedentary Lifestyle on Postural Control of Community-dwelling Old Adults - Uanderson Silva Pirôpo; Silvania Moraes Costa; Ícaro JS Ribeiro; Ivna Vidal Freire; Ludmila Schettino; Rafael da Silva Passos; Marco Machado; Cezar Augusto Casotti; Rafael Pereira (Sapientia Publishing Group, 2021)
OBJECTIVES The maintenance of the postural balance is fundamental for the daily living activities, as well as for the practice of physical exercise. However, the aging process and sedentary behavior (i.e., large sitting time) lead to changes biological systems, impairing postural balance with consequent increased falls risk. On the other hand, physical activity practice is a protective factor against these trends. The aim of this study is to investigate the influence of physical activity profile and sedentary behavior on postural control in community-dwelling old adults. METHODS This is a cross-sectional study including 208 community-dwelling old adults, which were stratified as sufficiently or insufficiently physically active and with or without sedentary behavior. Then, they were grouped as follow: G1 (sufficiently physically active and without sedentary behavior), G2 (insufficiently physically active, but without sedentary behavior), G3 (sufficiently physically active, but with sedentary behavior), and G4 (insufficiently physically active and with sedentary behavior). RESULTS Stabilometric parameters (sway area, total length of center of pressure [CoP] trajectory, and the mean velocity of CP displacement) were obtained to evaluate the postural control. There was significant difference between G1 and G4 on mean velocity of CoP displacement (p < 0.05). CONCLUSIONS The coexistence of sedentary behavior and insufficient physically active profile seem to impact negatively on postural control.